Mechanism underlying circRNA dysregulation in the TME of digestive system cancer - Wu, Zeyu; Yu, Xiao; Zhang, Shuijun; He, Yuting; Guo, Wenzhi (Frontiers in Immunology, 2022)
Cancer is the leading cause of health problems worldwide, and among all cancers, tumors of the digestive system occupy the dominant position. Therefore, the development of corresponding therapeutic targets and anticancer mechanisms is critical for the current research. Circular RNAs (circRNAs) are a new series of non-coding RNAs (ncRNAs) that have been reported to be expressed in eukaryotic cells. An increasing number of studies have demonstrated the important regulatory role of circRNA in various DSC. Furthermore, circRNA can recruit and reshape key cellular and stromal components of the tumor microenvironment to further influence the activation and inhibition of various signaling pathways, thereby affecting tumorigenesis. In this review, we summarize the role of circRNAs in the tumor microenvironment of the digestive system, including immune surveillance, angiogenesis, hypoxia, and chemical resistance. The regulation of the tumor microenvironment by circRNA is expected to be a new therapeutic method.